How many Welsh, Sámi, Sorbs … Are There? Numeric Data on Ethnicity and Language Speakers as Controversial Phenomenon - Leoš Šatava (HISTORICKÁ SOCIOLOGIE, 2023)
In connection with professional texts, statistics, encyclopedic entries or other information about ethnic communities, data on their abundance are also commonly mentioned. However, an apparently straightforward fact as ethnicity/ethnic identity, seemingly easy to measure exactly, is highly debatable, as it hides a number of pitfalls and difficult-to-answer questions; it is also easy to manipulate and misuse politically. The same applies to the no less vague and difficult-to-measure phenomena of knowledge/use of language or mother tongue and their registration. The main emphasis of the text is on the current specific problems of ethnic and linguistic records, which are documented and analyzed: 1/ at a general level; 2/ on several current examples of European minority ethnic groups (Welsh, Sámi, Sorbs, Kalmyks, Rusyns). The tradition of ethnic/linguistic censuses is strong especially in Central and Eastern Europe. The author documents this fact on the Czech example, which is still based on the Austro-Hungarian model. It follows from the above that the standard publication of results of ethnic and linguistic censuses – despite their widespread and apparent exactness – must be received, due to the controversial dimension present, with considerable caution.